ANALISIS EFEKTIVITAS PENANGANAN LIMBAH B3 RUMAH SAKIT BHAYANGKARA KOTA KENDARI - Munawir, Abdillah (Universitas Malahayati, 2024)
The fundamental problem regarding waste is its management and the impacts that will occur if the waste is not managed well or even not managed at all. Effectiveness of sustainable waste management at Bhayangkara Hospital, Kendari City. The aim of this study is to analyze the effectiveness of managing hazardous and toxic waste, organic wet waste and inorganic dry waste at the Bhayangkara hospital. The study method used was descriptive qualitative by conducting observations and in-depth interviews. Based on the data collected, Bhayangkara Kendari Hospital is strategically located in the eastern part of the city, so it can be accessed by public transportation from anywhere in Kendari. As a result of its operations, hospitals cause four main types of pollution: 1. Liquid waste management; 2. Management of air pollution; 3. Management of Hazardous and Toxic Materials; 4. Management of hazardous and toxic waste. The Bhayangkara hospital management has carried out intensive routine activities including management aspects of potential pollutants, especially hazardous and toxic waste, organic wet waste and inorganic dry waste.